L’insularità femminile ne Il sesso inutile di Oriana Fallaci - Tichoniuk-Wawrowicz, Ewa (Romanica Silesiana)
On her journey through various countries of Asia and the Pacific (e.g. the island of Hong Kong, Japan, the Hawaiian Islands), Fallaci was able to discover that the feminine insularity was dictated not only by the geographical reality. The periphericity of the condition of the “useless sex” seemed to her almost a sine qua non of femininity itself. The colonial center / periphery dichotomy strengthened on a special role of the Asian woman, who only with globalization of the twentieth century found herself forced to a painful confrontation with tradition on the one hand and with modernity on the other. Therefore, it seems interesting to analyze the results generated by the sociocultural tension observed by Fallaci and the changes onto‑epistemological caused by the revolution of costumes. Key words: woman, island, insularity, Oriana Fallaci, Asia